Membrane adsorption with polyacrylonitrile prepared with superfine powder-activated carbon, case study: separation process applied in water treatment containing diclofenac. Issue 4 (10th February 2022) - Carmo, Juliana do; Justino, Naiara Mottim; Matias, Marcelo Seleme; Puerari, Rodrigo Costa; Matias, William Gerson; Ladner, David; Vicentini, Denice Schulz; Nagel Hassemer, Maria Eliza
ABSTRACT: Polyacrylonitrile membranes (PAN) have high stability against chemical agents, making them suitable for a wide range of applications as such Ultrafiltration processes. Ultrafiltration membranes composed of PAN/Superfine powder activated carbon (S-PAC) mixtures can be a good research route, aiming the development of a new separation processes for water treatment. The association of materials to form a single product can have technological and economic advantages in separation processes. In this study, S-PAC impregnated into PAN membranes were prepared, characterized and used, as a case study, to remove diclofenac (DCF) from water. The membranes (PAN/S-PAC) were synthesized with different concentrations of S-PAC (0.2, 0.6, 1.0, 3.0 and 5.0 wt%) by a phase inversion process. The results of the TEM characterizations of the S-PAC indicated the presence of micro and nanoparticles (∼10 nm) and tending to form micrometric clusters. The infrared spectra of the membranes were characteristic of PAN; however, vibrational bands attributed to the S-PAC spectrum were also observed, which indicated an interaction between the materials. The case study showed an increase in the water flux and in the DCF rejection efficiency, for composite membranes (PAN/S-PAC) with higher concentration of S-PAC. The results of static adsorption tests indicated that the mechanism of DCF rejection occurred predominantly by adsorption. There were indications that the PAN/S-PAC membranes formed a composite material and the PAN/S-PAC (3.0) presented the best study composition given the results. Although the research is in its initial phase, the results indicated that the composition can improve many water treatment systems. GRAPHICAL ABSTRACT: UF0001